Phosphorylation Induced Conformational Transitions in DNA Polymerase β - Srivastava, Amit; Idriss, Haitham; Taha, Kamal; Lee, Sungmun; Homouz, Dirar (Frontiers in Molecular Biosciences, 2022)
DNA polymerase β (pol β) is a member of the X- family of DNA polymerases that catalyze the distributive addition of nucleoside triphosphates during base excision DNA repair. Previous studies showed that the enzyme was phosphorylated in vitro with PKC at two serines (44 and 55), causing loss of DNA polymerase activity but not DNA binding. In this work, we have investigated the phosphorylation-induced conformational changes in DNA polymerase β in the presence of Mg ions. We report a comprehensive atomic resolution study of wild type and phosphorylated DNA polymerase using molecular dynamics (MD) simulations. The results are examined via novel methods of internal dynamics and energetics analysis to reveal the underlying mechanism of conformational transitions observed in DNA pol β. The results show drastic conformational changes in the structure of DNA polymerase β due to S44 phosphorylation. Phosphorylation- induced conformational changes transform the enzyme from a closed to an open structure. The dynamic cross-correlation shows that phosphorylation enhances the correlated motions between the different domains. Centrality network analysis reveals that the S44 phosphorylation causes structural rearrangements and modulates the information pathway between the Lyase domain and base pair binding domain. Further analysis of our simulations reveals that a critical hydrogen bond (between S44 and E335) disruption and the formation of three additional salt bridges are potential drivers of these conformational changes. In addition, we found that two of these additional salt bridges form in the presence of Mg ions on the active sites of the enzyme. These results agree with our previous study of DNA pol β S44 phosphorylation without Mg ions which predicted the deactivation of DNA pol β. However, the phase space of structural transitions induced by S44 phosphorylation is much richer in the presence of Mg ions.